A series of in vitro and human studies of a novel lip cream formulation for protecting against environmental triggers of recurrent herpes labialis - Gfeller CF; Wanser R; Mahalingam H; Moore DJ; Wang X; Lin CB; Shanga G; Grove G; Rawlings AV (Dove Medical Press, 2019)
Christoph F Gfeller,1 Rita Wanser,2 Harish Mahalingam,2 David J Moore,3 Xuying Wang,4 Connie B Lin,4 Gilbert Shanga,5 Gary Grove,6 Anthony V Rawlings7 1GlaxoSmithKline Consumer Healthcare, Medical Affairs Skin Health, Weybridge, Surrey, UK; 2GlaxoSmithKline Consumer Healthcare, Medical Affairs Skin Health, Warren, NJ, USA; 3GlaxoSmithKline Consumer Healthcare, R&D Innovation Skin Health, Weybridge, Surrey, UK; 4GlaxoSmithKline Consumer Healthcare, R&D Innovation Skin Health, Collegeville, PA, USA; 5GSK Consumer Healthcare, Biostatistics, Warren, NJ, USA; 6cyberDERM, Inc., Broomall, PA, USA; 7AVR Consulting, Ltd., Cheshire, UK Purpose: These studies describe the testing of a novel, daily-use lip cream designed for individuals with lips prone to recurrent herpes labialis (RHL) that protects against environmental triggers.Subjects and methods: In vitro occlusive and in vitro and in vivo photoprotection analyses, a characterization of normal vs dry lips, and a randomized, evaluator-blinded, clinical trial that assessed the lip cream in healthy subjects with dry lips were conducted. In the clinical trial, subjects applied the lip cream or were untreated and evaluated using transepidermal water loss (TEWL), corneometry, visual assessments of lip dryness, expert photographic evaluations, and subject-rated outcomes.Results: The lip cream’s in vitro water vapor transmission rate (84.1 g/(m2 h)) indicated moderate occlusivity. The lip cream, but not placebo or control (water), reduced ultraviolet A (UVA)- and UVB-induced DNA damage, and tumor necrosis factor-α (EpiDermFT) and prostaglandin E2 release (EpiDermFT and EpiGingival™). The lip cream’s in vivo sun protection factor (SPF) was 12.2 (lower confidence limit, 11.3) and SPF/UVA protection factor ratio was 0.9. The characterization of dry vs normal lips identified differences in moisturization. In the clinical trial, the lip cream significantly decreased TEWL (difference: –7.19 [95% CI: −11.41, –2.98]; P<0.01), increased corneometry (difference: 4.62 [95% CI: 1.05, 8.19]; P<0.05), and reduced visual dryness (difference: –1.48 [95% CI: 2.24, –0.71]; P<0.001) compared to untreated subjects. Significant benefits were also observed on expert photographic assessments of scaling (difference: –0.89 [95% CI: −1.75, –0.03]; P< 0.05), cupping (difference: –1.50 [95% CI: −2.30, –0.70]; P<0.001), and healthy appearance (difference: –1.44 [95% CI: −2.29, –0.58]; P<0.01); differences in overall healthy appearance were not significant (P=0.51). Subject-rated assessments indicated improvements in cracking, dryness, and flaking in the lip cream group but worsening in untreated subjects.Conclusion: These studies indicate that this novel, daily-use lip cream protects against UV radiation, drying, and chapping, which are established environmental RHL triggers. Keywords: herpes simplex virus, barrier function, lip care, UV radiation